The Metabolites of Lactobacillus fermentum F-B9-1 Relieved Dextran Sulfate Sodium-Induced Experimental Ulcerative Colitis in Mice - Su, Le; Ma, Feifan; An, Zaiyong; Ji, Xiuyu; Zhang, Ping; Yue, Qiulin; Zhao, Chen; Sun, Xin; Li, Kunlun; Li, Baojun; Liu, Xinli; Zhao, Lin (Frontiers in Microbiology, 2022)
Because of the increased incidence and prevalence, ulcerative colitis (UC) has become a global health issue in the world. Current therapies for UC are not totally effective which result in persistent and recurrent symptom of many patients. Lactobacillus with anti-inflammatory effects might be beneficial to the prevention or treatment for UC. Here, we examined the ameliorative effects of the metabolites of Lactobacillus fermentum F-B9-1 (MLF) in Caco-2 cells and dextran sodium sulfate (DSS)-induced UC model mice. MLF displayed intestinal barrier-protective activities in Caco-2 cells by increasing the expression of Occludin and ZO-1. They also showed anti-inflammatory potential in interleukin (IL)-1β and IL-6. In order to further examine the in vivo anti-inflammatory effect of MLF, the MLF was gavaged in the DSS-induced UC model mice. The intragastric administration of MLF effectively alleviated colitis symptoms of weight loss, diarrhea, colon shortening, and histopathological scores, protected intestinal barrier function by increasing Occludin and ZO-1, and attenuated colonic and systemic inflammation by suppressing production of IL-1β and IL-6. Finally, the use of MLF remodeled the diversity of the gut microbiota and increased the number of beneficial microorganisms. Overall, the results demonstrated that MLF relieved DSS-induced UC in mice. And MLF might be an effective therapy method to UC in the clinic in the future.